Cut-off Score of Indonesian Version of Sensorimotor History Questionnaire for Preschooler and Soft Sign Cambridge Neurological Inventory against Intelligent Quotient - Siti Aminah Sobana; Tiara Pramaesya; Uni Gamayani; Lisda Amalia; Suryani Gunadharma; Andi Basuki Prima Birawa (Faculty of Medicine, Universitas Padjadjaran, 2021)
Early detection of Sensory Processing Disorder (SPD) is important for deciding on appropriate interventions for children at risk. However, there is no valid screening tool available at this moment. The purpose of this study was to validate the deGangi, Sensorimotor History Questionnaire for Preschooler (SHQP), and neurological soft sign of Cambridge Neurological Inventory (NSS CNI) against intelligent quotient (IQ) to establish a reliable cut-off for SPD screening tools for children aged 4–6 years. Sixty-four parent-child were recruited randomly from 3 kindergartens in Bandung, Indonesia. Eligible parents were asked to fill out the SHQP, while their child was assessed using theWechsler Preschool and Primary Scale of Intelligent (WPPSI) and NSS CNI. The deGangi SHQP score and NSS CNI showed a weak and moderate correlation with Full-scale IQ (FIQ). The total score of deGangi SHQP’s sensitivity was 50% with a specificity of 53.4% and a negative predictive value (NPV) of 91.2% agaisnt the FIQ score. The total sensitivity for the NSS CNI was 66.7%, while the total specificity was 58.6% and the NPV was 94.4%. Meanwhile, the sensitivity for the sensory integration subscale score of the NSS CNI was 83.3%, with a specificity of 60.3% and an NPV of 97.2%. The deGangi SHQP can be considered to be an SPD screening tool with the cut-off scores for each subscale of self-regulation, sensory processing of touch, sensory processing of movement, emotional maturity, and motor maturity of 3, 3, 3, and 2, respectively, while the NSS CNI can be used for identifying SPD in children aged 4–6 years with a cut-off scores for the motor coordination, sensory integration, and disinhibition subscales of 7, 10, and 3, respectively.